Tasteonus: The Recipe Mobile Application - Han, Oii Yee; Majid, Nur Amira Abdul; Salleh, Masrina A. (Journal of Applied Technology and Innovation, 2023)
The mobile technology revolution significantly impacted daily human activities, including cooking. The cooking trend has changed to a new concept called the "digital kitchen." It is a novel concept in cooking and illustrates the culinary process of preparing a dish while using cell phones. Unfortunately, one of the main problems caused by poor connectivity is the accessibility of the current recipe mobile application. In fact, retaining client loyalty and the absence of video instructions alongside the recipes made it difficult for any recipe app to remain competitive in this market. This recipe mobile app, Tastenous, employed JavaScript for the programming language, and Expo CLI 5.2.0, React Native 0.67, and Postman 9.14.0 for the libraries/tools, while SQLite 6.0.1 and MySQL 8.0 were chosen for database management. Windows 10, Android 12, iOS 15.3.1 for the operating system, and finally Heroku 7.59.3 for the web server. A mobile recipe software developed, Tasteonus, employs video technology to display movies alongside published recipes and to allow apps to function both online and offline. Additionally, gamification techniques are being employed to increase user engagement and preserve consumer loyalty. The offline mode and built-in video technology allow users to continue following previously saved recipes even when there is no online connection. Future improvements should concentrate on the best ways to implement the gamification notion, including adding leaderboards to the software. The apps ought to include a reward system that people can’t misuse. The rewards that were promised in the application should also be available when the user redeems it.